Preparation method of high-entropy phosphorus-fluoride nanoparticle catalyst, prepared catalyst and oxygen evolution electrode

The high-entropy phosphorus-fluoride nanoparticle catalyst was synthesized at room temperature by droplet-particle method, which solved the requirements of high-temperature equipment and nanoscale synthesis problems in the existing technology, and achieved efficient and stable catalytic performance.

CN119640313AActive Publication Date: 2025-03-18ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411745789.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The prior art is difficult to synthesize high entropy material (HEMs) catalysts under mild conditions, especially at the nanoscale, and most synthesis methods require high temperature and specialized equipment.

Method used

The droplet-particle method was used to dissolve five metal salts in anhydrous ethanol, and the metal ions were encapsulated in ethanol droplets by sonication and atomization technology. These droplets were then blown into the ammonium hydroxide solution for reaction to form a precursor, and reacted with PH3 and HF in an oxygen-free environment to prepare a high entropy phosphorus-fluoride nanoparticle catalyst.

Benefits of technology

The high entropy phosphorus-fluoride nanoparticle catalyst was synthesized under normal temperature and pressure, reducing the preparation temperature (only 300-700℃), simplifying equipment requirements, and improving the electrochemical stability and catalytic activity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640313A_ABST
    Figure CN119640313A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolysis water catalysis, and particularly relates to a preparation method of a high-entropy phosphorus-fluoride nanoparticle catalyst, the prepared catalyst and an oxygen evolution electrode. The preparation method of the high-entropy phosphorus-fluoride nanoparticle catalyst comprises the following steps: dissolving soluble metal salts of Ni, Fe, Cu, Co and Mn in distilled water or / and ethanol to prepare a metal salt solution with the concentration of 0.005 mol / L, atomizing the solution into micro-nano aerosol liquid drops, blowing the aerosol liquid drops into an ammonium hydroxide solution, carrying out suction filtration and drying after atomization is finished, and carrying out vacuum drying to obtain the high-entropy phosphorus-fluoride nanoparticle catalyst. Precursor powder is obtained; then the precursor powder respectively reacts with PH3 and HF in an oxygen-free environment, and the high-entropy phosphorus-fluoride nanoparticle catalyst is obtained after the reaction is finished. According to the preparation method disclosed by the invention, the precursor can be synthesized at normal temperature and normal pressure, and the temperature for preparing the high-entropy phosphorus-fluoride nanoparticle catalyst is only 500 DEG C, which is obviously lower than that of a traditional high-entropy alloy melt forging preparation technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic water catalysis, and specifically relates to a method for preparing a high-entropy phosphorus-fluoride nanoparticle catalyst, and also relates to the prepared catalyst and an oxygen evolution electrode using the catalyst. Background Art

[0002] In recent years, catalysts based on high entropy materials (HEMs) have been widely used to reduce the energy consumption of oxygen evolution reaction (OER). In the earliest studies, high entropy materials (HEMs) were defined as new materials with a single crystal structure composed of five or five elements with an atomic ratio of 5-35%. Although this qualitative description of HEMs is direct and useful, it lacks clear boundary conditions. Therefore, people later defined materials with a configurational entropy greater than or equal to 1.5 R as high entropy systems. HEMs have four "core effects", including the high entropy effect in thermodynamics, the lattice distortion effect in structure, the hysteresis diffusion effect in kinetics, and the "cocktail" effect in performance. These unique properties make them have potential application value in many fields. Among them, the high entropy effect refers to the fact that the high configurational entropy of HEMs makes materials containing five or more metal elements in nearly / equimolar ratios more inclined to form a single-phase solid solution (rather than an intermetallic compound). The hysteresis diffusion effect means that due to the high diffusion energy barrier, unlike the uniform diffusion of traditional alloys, the diffusion and phase change of atoms in HEMs are very slow. These two effects endow HEMs with excellent electrochemical stability and corrosion resistance, making them the focus of researchers in the field of water electrolysis catalysis.

[0003] In order to significantly improve the electrocatalytic performance, the starting point of the design of electrocatalysts is mainly to increase the number of active sites, change the coordination environment, and improve the electronic structure. Therefore, the design strategy of advanced multi-principal metal-based catalysts should not only focus on the design of components, but also on the control of their morphology. As we all know, in order for a catalyst to exert its catalytic effect, it must be in direct contact with the reactants, and nanomaterials happen to have outstanding advantages in this regard. For HEMs, when they are reduced to the nanoscale, the large surface area, high potential energy, obvious lattice distortion and significant synergistic effect make nanosized HEMs an ideal catalyst for OER.

[0004] To obtain nanosized HEMs, people have explored a variety of methods, including biomass templates, MOFs templates, and non-template methods. Among them, non-template methods show particular promise due to the wet chemical method's precision in controlling size, morphology, and composition. However, a challenge remains: most synthetic compounds contain only three elements or less. This limitation stems from the obvious immiscibility during the synthesis process. Although high entropy effects can promote the formation of homogeneous phases, strict conditions, such as increasing the heating temperature, are required to achieve the optimal mixing entropy. Therefore, there is an urgent need for a method to synthesize HEMs under mild conditions. Summary of the invention

[0005] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a method for preparing a high-entropy phosphorus-fluoride nanoparticle catalyst, and also provide the prepared catalyst and an oxygen evolution electrode using the catalyst.

[0006] Based on the above purpose, the present invention adopts the following technical solution: The present invention provides a method for preparing a high entropy phosphorus-fluoride nanoparticle catalyst, comprising the following steps: S1: Dissolve soluble metal salts of Ni, Fe, Cu, Co, and Mn in distilled water or / and ethanol to prepare a 0.001-0.1 mol / L metal salt solution, and perform ultrasonic treatment to mix the solution evenly; atomize the solution into micro-nano-sized aerosol droplets and blow them into an ammonium hydroxide solution. After atomization, filter and dry to obtain a precursor powder; S2: The precursor powder is reacted with PH3 and HF in an oxygen-free environment to obtain (FeCoNiCuMn)P2 / (FeCoNiCuMn)F2 heterogeneous nanoparticles, which are then washed with water to obtain a high entropy phosphorus-fluoride nanoparticle catalyst.

[0007] Furthermore, the size of the aerosol droplets is 2-4 μm.

[0008] Furthermore, the soluble metal salts of Ni, Fe, Cu, Co, and Mn can be selected from any one of the corresponding nitrates, sulfates, chlorides, and acetates. When preparing soluble metal salt solutions of Ni, Fe, Cu, Co, and Mn, the solvent can be selected from distilled water, anhydrous ethanol, or an aqueous solution of ethanol; when the solvent is distilled water, the reaction speed of the aerosol droplets atomized from the metal salt solution and the ammonium hydroxide solution is very fast, and the generated precursor powder particles are larger in size, and the precursor powder particle size ranges from hundreds of nanometers to tens of microns; when the solvent is ethanol, the reaction speed of the aerosol droplets atomized from the metal salt solution and the ammonium hydroxide solution slows down, and the generated precursor powder particles are smaller in size, and the precursor powder particle size ranges from tens to hundreds of nanometers. In order to better control the particle size of the precursor powder, the solvent is preferably anhydrous ethanol.

[0009] Furthermore, when the aerosol droplets are blown into the ammonium hydroxide solution for reaction, the aerosol generated by atomization can be continuously sprayed onto the interface of the ammonium hydroxide solution, or the pipeline for conveying the aerosol can be passed into the interior of the ammonium hydroxide solution for reaction. This process is relatively slow. The volume ratio of the metal salt solution to the ammonium hydroxide solution before atomization is about 1:1. It takes 10 to 16 hours to completely atomize an equal volume of the metal salt solution. After atomization and blowing are completed, the reaction can be terminated, and subsequent operations such as filtration and drying can be performed.

[0010] Furthermore, the specific process of the reaction between the precursor powder and PH3 in step S2 is as follows: NaH2PO2 is placed upstream of the reactor, the precursor powder is spread downstream of the reactor, an inert gas is introduced from upstream to downstream, and the reactor is heated to thermally decompose NaH2PO2, and the PH3 produced by thermal decomposition is carried downstream by nitrogen or inert gas to react with the precursor powder for phosphating. NaH2PO2 and the precursor powder should avoid contact, and preferably keep a certain distance (3 to 5 cm) to prevent the residue after the thermal decomposition of NaH2PO2 from contaminating the product.

[0011] Furthermore, the temperature of the phosphating reaction is 250-550°C.

[0012] Furthermore, the specific process of the reaction between the precursor powder and HF in step S2 is: placing NH4F upstream of the reactor, spreading the precursor powder downstream of the reactor, introducing an inert gas from upstream to downstream, and heating the reactor to thermally decompose NH4F. The HF produced by the thermal decomposition is carried downstream by nitrogen or inert gas to undergo a fluorination reaction with the precursor powder.

[0013] Furthermore, the temperature of the fluorination reaction is 300-700°C.

[0014] Furthermore, the inert gas is Ar gas, and the Ar gas flow rate during the phosphating and fluoriding process is 50 ml / min; phosphating is performed first and then fluoriding, NaH2PO2 and NH4F are supplied in excess, the phosphating time is 2 to 3 hours, and the fluoriding time is 5 to 30 minutes. Adequate phosphorus source supply and 2 to 3 hours of phosphating time can ensure that the phosphating reaction is fully carried out; then, the amount of phosphide converted to fluoride is controlled by controlling the fluoridation time to adjust the proportion of (FeCoNiCuMn)P2 and (FeCoNiCuMn)F2 components in the product.

[0015] Furthermore, since the atomization and blowing process of the metal salt solution takes a long time, and the ammonia in the ammonium hydroxide solution is very volatile, the ammonium hydroxide solution is selected to be ammonia water with an ammonia concentration of ≥20wt%.

[0016] The present invention also provides a high entropy phosphorus-fluoride nanoparticle catalyst prepared by the above preparation method.

[0017] The present invention also provides an oxygen evolution electrode prepared by using the high entropy phosphorus-fluoride nanoparticle catalyst.

[0018] Furthermore, the preparation steps of the electrode are: The carbon rod (CR, 5 mm in diameter, 100 mm in length) was soaked in 1.0 M H2SO4 solution for 1 h to remove impurities, and then soaked in anhydrous ethanol for 3 h to improve hydrophilicity; 0.03 g of the high entropy phosphorus-fluoride nanoparticle catalyst sample powder was dispersed in a mixture of 490 μL anhydrous ethanol, 490 μL deionized water and 20 μL Nafion dispersion solution; then stirred in an ice water bath for 30 min with the assistance of ultrasound to obtain a uniform slurry. Further, 20 μL of the slurry was evenly applied to the surface of the pretreated carbon rod and dried at room temperature for 24 h to obtain an electrode.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation of HEMs catalysts is often challenging due to the different deposition thermodynamics of different ions. Achieving uniform distribution of multiple elements in nanoparticles (NPs) requires high temperatures (usually over 1000 °C), cumbersome procedures, and specialized equipment. 3+ 、Co 2+ 、Ni 2+ , Cu 2+ and Mn 2+ The ions are encapsulated in ethanol droplets. When these droplets carrying ions are blown into ammonium hydroxide solution, a large amount of OH - ions envelop and separate these microdroplets. Subsequently, these OH -ions react with different metal ions to form precursors. In this droplet environment, metal ions are continuously exposed to OH - ions, which helps them to be rapidly converted into hydroxide NPs. The present invention effectively alleviates the challenges brought by the different reaction thermodynamics of different ions. By confining the reaction within the droplet, the element ratio in the precursor is closely consistent with the initial solution.

[0020] (2) In addition, the separation of each droplet by the ammonium hydroxide solution limits the diffusion of ions and hinders unnecessary volume accumulation. As a result, a uniform ink-like suspension can be obtained. The resulting precursor exhibits a flocculent microstructure that keeps it suspended in the droplets. After phosphating and fluorinating, the hydroxide floccules are transformed into heterogeneous nanoparticles. The in situ and localized transformation process ensures that the obtained (FeCoNiCuMn)P2 / (FeCoNiCuMn)F2 (FeCoNiCuMn high entropy phospho-fluoride) composite has a good microscopic contact interface between its (FeCoNiCuMn)P2 and (FeCoNiCuMn)F2 components. If the ammonium hydroxide solution is replaced with other strongly alkaline solutions (such as NaOH solution), it is found that the droplets are destroyed, resulting in the formation of a blocky morphology, which may be due to the faster reaction rate.

[0021] (3) It is worth noting that the present invention synthesizes the precursor at room temperature and pressure. The preparation temperature of the (FeCoNiCuMn)P2 / (FeCoNiCuMn)F2 composite material is only 300-700°C, which is significantly lower than the traditional HEMs preparation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the synthesis and preparation process of FeCoNiCuMn high entropy phosphorus-fluoride catalyst; Figure 2 The OER catalytic performance, electrochemical impedance spectroscopy and response current stability test results of the samples of Example 1, Comparative Example 1 and Comparative Example 2 are shown; Figure 3 The results of structural and component characterization of different samples are shown in Figure 2. Figure 4 The OER catalytic performance and electrochemical impedance test results of samples obtained at different fluorination times; Figure 5 The test results of OER catalytic performance and electrochemical impedance of samples with different elemental compositions. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through embodiments in combination with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] (I) Discussion on phosphating and fluorinating reactions in the preparation of high entropy phosphorus-fluoride nanoparticle catalysts Example 1 A method for preparing a high entropy phosphorus-fluoride nanoparticle catalyst, such as Figure 1 As shown, the following steps are included: S1: The precursor was prepared by the droplet-particle method: five metal salts, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, Co(NO3)2 and Mn(NO3)2, were dissolved in anhydrous ethanol to prepare a metal salt solution with an equimolar concentration (0.005 mol / L). The metal salt solution was then ultrasonicated for 30 min to mix the solution evenly. The solution was then atomized with an Owegels medical nebulizer to produce aerosol droplets of micro-nano size (about 2 μm). The aerosol droplets containing metal ions were blown into the ammonium hydroxide solution with air. Each droplet was used as a microreactor to be hydrated by OH. - After the atomization is completed, the ammonium hydroxide solution of the collected aerosol droplets is filtered, and the precipitate obtained by filtration is placed in a vacuum oven at 30°C for drying to obtain a precursor powder.

[0025] S2: The precursor powder is reacted with PH3 and HF in an oxygen-free environment to perform phosphating and fluoriding treatments.

[0026] (1) Phosphating treatment: About 1.0 g of NaH2PO2 was placed in the upstream of the quartz tube furnace, and 0.5 g of the precursor powder was spread in the downstream of the quartz tube furnace. The two were prevented from contacting each other. Ar gas was introduced from the upstream to the downstream. At the same time, the quartz tube furnace was heated to thermally decompose NaH2PO2. The PH3 produced by the thermal decomposition of NaH2PO2 was carried downstream by the Ar gas to react with the precursor powder for phosphating. The phosphating reaction temperature was 350 °C and the reaction time was 2 h. After the phosphating reaction, the (FeCoNiCuMn)P2 material was obtained.

[0027] (2) Fluorination treatment: 1.0 g NH4F was placed in the upstream of the quartz tube furnace, and the (FeCoNiCuMn)P2 material obtained by phosphating treatment was spread in the downstream of the quartz tube furnace. Ar gas was introduced from the upstream to the downstream, and the quartz tube furnace was heated to thermally decompose NH4F. The HF produced by the thermal decomposition of NH4F was carried downstream by the Ar gas to react with the (FeCoNiCuMn)P2 material for fluorination. The fluorination reaction temperature was 500 °C and the reaction time was 15 min. After the fluorination reaction, the (FeCoNiCuMn)P2 / (FeCoNiCuMn)F2 heterogeneous nanoparticle catalyst was obtained.

[0028] Comparative Example 1 A method for preparing a high entropy phosphide nanoparticle catalyst comprises the following steps: S1: The precursor was prepared by the droplet-particle method: five metal salts, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, Co(NO3)2 and Mn(NO3)2, were dissolved in anhydrous ethanol to prepare a metal salt solution with an equimolar concentration (0.005 mol / L). The metal salt solution was then ultrasonicated for 30 min to mix the solution evenly. The solution was then atomized with an Owegels medical nebulizer to produce aerosol droplets of micro-nano size (about 2 μm). The aerosol droplets containing metal ions were blown into the ammonium hydroxide solution with air. Each droplet was used as a microreactor to be hydrated by OH. - After the atomization is completed, the ammonium hydroxide solution of the collected aerosol droplets is filtered, and the precipitate obtained by filtration is placed in a vacuum oven at 30°C for drying to obtain a precursor powder.

[0029] S2: Phosphating treatment: About 1.0 g NaH2PO2 was placed in the upstream of the quartz tube furnace, and 0.5 g precursor powder was spread in the downstream of the quartz tube furnace, and the two were prevented from contacting each other. Ar gas was introduced from the upstream to the downstream, and the quartz tube furnace was heated to thermally decompose NaH2PO2. PH3 produced by the thermal decomposition of NaH2PO2 was carried downstream by the Ar gas to react with the precursor powder for phosphating. The phosphating reaction temperature was 350 ° C, and the reaction time was 2 h. After the phosphating reaction, (FeCoNiCuMn)P2 material was obtained. The product was rinsed with distilled water to obtain FeCoNiCuMn high entropy phosphide nanoparticle catalyst.

[0030] Comparative Example 2 A method for preparing a high entropy fluoride nanoparticle catalyst comprises the following steps: S1: The precursor was prepared by the droplet-particle method: five metal salts, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, Co(NO3)2 and Mn(NO3)2, were dissolved in anhydrous ethanol to prepare a metal salt solution with an equimolar concentration (0.005 mol / L). The metal salt solution was then ultrasonicated for 30 min to mix the solution evenly. The solution was then atomized with an Owegels medical nebulizer to produce aerosol droplets of micro-nano size (about 2 μm). The aerosol droplets containing metal ions were blown into the ammonium hydroxide solution with air. Each droplet was used as a microreactor to be hydrated by OH. - After the atomization is completed, the ammonium hydroxide solution of the collected aerosol droplets is filtered, and the precipitate obtained by filtration is placed in a vacuum oven at 30°C for drying to obtain a precursor powder.

[0031] S2: Fluorination treatment: about 1.0 g NH4F was placed in the upstream of the quartz tube furnace, and 0.5 g of precursor powder was spread in the downstream of the quartz tube furnace. Ar gas was introduced from the upstream to the downstream, and the quartz tube furnace was heated to thermally decompose NH4F. The HF produced by the thermal decomposition of NH4F was carried downstream by the Ar gas to react with the precursor powder for fluorination. The fluorination reaction temperature was 500 ° C, and the reaction time was 15 min. After the fluorination reaction, (FeCoNiCuMn)F2 material was obtained. After rinsing with distilled water, FeCoNiCuMn high entropy fluoride nanoparticle catalyst was obtained.

[0032] The samples of Example 1, Comparative Example 1 and Comparative Example 2 were prepared as oxygen evolution electrodes, and the OER catalytic performance of the high entropy catalyst was evaluated. Compared with FeCoNiCuMn high entropy fluoride and FeCoNiCuMn high entropy phosphide, the optimized FeCoNiCuMn high entropy phosphide electrode showed better catalytic activity, requiring only 209 mV@10 mA cm in alkaline solution. -2 and 346mV@100mAcm -2 ( Figure 2 a).

[0033] In addition, the charge transfer resistances of FeCoNiCuMn high entropy phospho-fluoride, FeCoNiCuMn high entropy fluoride, and FeCoNiCuMn high entropy phosphide are 1.7Ω, 7.4Ω, and 3.7Ω, respectively. Figure 2 b). This indicates that FeCoNiCuMn high entropy phosphorus-fluoride has a higher charge transfer rate, faster reaction kinetics and better electrocatalytic performance for oxygen evolution reaction. FeCoNiCuMn high entropy phosphorus-fluoride catalyst shows good stability. In the first ten hours of the test, due to the activation reaction (increase in transition metal valence state), the corresponding current of the electrode increases ( Figure 2 c).

[0034] Furthermore, the samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to structural and component characterization analysis. Figure 3 As shown. It can be seen that the catalyst precursor presents a spherical structure, and the interior is mainly composed of water and metal hydroxide ( Figure 3 a, 3b). Figure 3 c HEP and Figure 3 From the XRD spectra of HEF and HEPF of d, it can be seen that the crystal structure of the high entropy phosphide is similar to the CoP2 phase (JCPDS 77-0263), but slightly shifted to the right, indicating that its lattice spacing is smaller. On the contrary, the crystal structure of the high entropy fluoride is similar to the CoF2 phase (JCPDS 77-0653), and the characteristic peak shifts to the left, indicating that the lattice spacing is larger. In addition, the crystal structure of the high entropy phosphorus-fluoride mainly reflects the high entropy fluoride phase, while the high entropy phosphide peak is obscured, which may be caused by the coating of the high entropy fluoride. The morphologies of FeCoNiCuMn high entropy phosphorus-fluoride, FeCoNiCuMn high entropy fluoride, and FeCoNiCuMn high entropy phosphide catalysts are shown in Figure 2. Figure 3 As shown in (eg), all catalysts exhibit porous nanoparticle structures, which can expose abundant catalytic active sites and large specific surface area, which is beneficial to enhance the diffusion and mass transfer of ions during the reaction. Figure 3 As shown in the EDS spectrum in h, the metal elements (Fe, Co, Ni, Cu and Mn) and non-metal elements (P, F, N and O) in HEPF are evenly distributed without obvious element segregation. Combined with XRD, it is proved that high entropy material is obtained.

[0035] (II) Discussion on the fluorination time in the preparation method of high entropy phosphorus-fluoride nanoparticle catalyst Example 2 The content of the preparation method of a high entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the fluorination time is 5 min.

[0036] Example 3 The content of the preparation method of a high entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the fluorination time is 30 min.

[0037] Example 4 The content of the preparation method of a high entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the fluorination time is 120 min.

[0038] The molar ratio of high entropy phosphide to high entropy fluoride in the catalyst samples prepared in Examples 1 to 4 was tested, and the results are shown in Table 1.

[0039] Table 1 Molar ratio of phosphide to fluoride in high entropy phosphorus-fluoride The present invention adopts the method of phosphating first and then fluorinating to synthesize the high entropy phosphorus-fluoride nanoparticle catalyst composite material, and finds that the molar ratio of high entropy phosphide to high entropy fluoride in the composite material is highly dependent on the fluorination time. As can be seen from Table 1, the molar ratio of F:P increases with the increase of fluorination time, indicating that more high entropy fluoride is formed.

[0040] Furthermore, the samples of Examples 1 to 4 were prepared as electrodes, and the catalytic activity and electrochemical resistance of the corresponding electrode materials obtained at different fluorination times were discussed and analyzed. The experimental method is as follows: The electrochemical workstation (CHI 760E) adopted a three-electrode system, with the prepared electrode, carbon rod electrode and Ag / AgCl electrode as the working electrode, counter electrode and reference electrode, respectively, to test the electrochemical performance of the catalyst. All electrochemical experiments were carried out in an electrolytic cell containing 1.0 M KOH. The catalytic activity of water electrolysis was determined by linear sweep voltammetry (LSV, scan rate of 2 mV s-1). The OER kinetics of the catalyst was characterized by electrochemical impedance spectroscopy (EIS). The ohmic resistance (Rs) was obtained from the high-frequency region, and the charge transfer resistance (Rct) value was obtained by simulating the arc radius of the Nyquist plot. Electrochemical impedance spectroscopy analysis was carried out in the frequency range of 0.05 Hz ~ 0.1 MHz, and the results are shown in Figure 4 shown.

[0041] Depend on Figure 4 It can be seen that the high entropy phosphorus-fluoride nanoparticle catalyst composite material prepared when the fluorination time is 15 min has the highest catalytic activity and the lowest electrochemical resistance.

[0042] 3. Discussion on the Type and Quantity of Metal Ions in the Preparation Method of High Entropy Phosphorus-Fluoride Nanoparticle Catalysts Comparative Example 3 The content of a preparation method of a medium-entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the metal salts are Ni(NO3)2, Fe(NO3)3, and Co(NO3)2, and FeCoNi medium-entropy phosphorus-fluoride is prepared by this method.

[0043] Comparative Example 4 The preparation method of a medium-entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the metal salts are four kinds, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, and Co(NO3)2. By this method, FeCoNiCu medium-entropy phosphorus-fluoride is obtained.

[0044] Comparative Example 5 The preparation method of a high-entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the metal salts are five kinds, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, Co(NO3)2, and Y(NO3)3. By this method, FeCoNiCuY high-entropy phosphorus-fluoride is obtained.

[0045] Comparative Example 6 The preparation method of a high-entropy phosphorus-fluoride nanoparticle catalyst is basically the same as that of Example 1, except that the metal salts are ten kinds, namely Ni(NO3)2, Fe(NO3)3, Cu(NO3)2, Co(NO3)2, Y(NO3)3, Mn(NO3)2, Al(NO3)3, Mg(NO3)2, Ca(NO3)2, and La(NO3)2. By this method, FeCoNiCuMnYAlMgCaLa high-entropy phosphorus-fluoride is obtained.

[0046] The samples of Example 1 and Comparative Examples 3-6 were prepared into electrodes, and the catalytic activity and electrochemical resistance of the corresponding electrode materials obtained under different element types and quantities in the catalyst were discussed and analyzed. The results are as Figure 5 shown: As Figure 5 shown, the influence of different element types and quantities on the performance of the electrocatalyst is demonstrated. The catalytic activity has no linear correlation with the entropy increase (element types), and the element types play a more crucial role in determining the catalytic activity. When the number of element types increases from 3 to 5, the response current density of the catalyst increases significantly, as Figure 5 shown in a. The OER catalytic activities of the medium-entropy phosphorus-fluoride and high-entropy phosphorus-fluoride are in the order of: FeCoNi medium-entropy phosphorus-fluoride < FeCoNiCu medium-entropy phosphorus-fluoride < FeCoNiCuMnYAlMgCaLa high-entropy phosphorus-fluoride < FeCoNiCuY high-entropy phosphorus-fluoride < FeCoNiCuMn high-entropy phosphorus-fluoride. The electrochemical impedance spectroscopy (EIS) further shows that compared with other medium-entropy phosphorus-fluorides or high-entropy phosphorus-fluorides, the charge transfer resistance (Rct) of FeCoNiCuMn high-entropy phosphorus-fluoride is significantly reduced (as Figure 5 shown in b).

Claims

1. A method for preparing a high entropy phosphorus-fluoride nanoparticle catalyst, characterized in that: The steps include: S1: Dissolve soluble metal salts of Ni, Fe, Cu, Co, and Mn in distilled water or / and ethanol to prepare a metal salt solution with a concentration of 0.001 to 0.1 mol / L, and perform ultrasonic treatment to mix the solution evenly; atomize the solution into micro-nano-sized aerosol droplets and blow them into an ammonium hydroxide solution, and after atomization, filter and dry to obtain a precursor powder; S2: The precursor powder is reacted with PH3 and HF in an oxygen-free environment to obtain (FeCoNiCuMn)P2 / (FeCoNiCuMn)F2 heterogeneous nanoparticles, which are then washed with water to obtain a high entropy phosphorus-fluoride nanoparticle catalyst.

2. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 1, characterized in that: The size of the aerosol droplets is 2-4 μm.

3. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 1, characterized in that: The specific process of the reaction between the precursor powder and PH3 in step S2 is: placing NaH2PO2 upstream of the reactor, spreading the precursor powder downstream of the reactor, introducing an inert gas from upstream to downstream, and heating the reactor at the same time to thermally decompose NaH2PO2. The PH3 produced by the thermal decomposition is carried downstream by nitrogen or inert gas to undergo a phosphating reaction with the precursor powder.

4. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 3, characterized in that: The temperature of the phosphating reaction is 250-550°C.

5. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 2, characterized in that: The specific process of the reaction between the precursor powder and HF in step S2 is as follows: NH4F is placed upstream of the reactor, the precursor powder is spread downstream of the reactor, an inert gas is introduced from upstream to downstream, and the reactor is heated to thermally decompose NH4F. The HF produced by the thermal decomposition is carried downstream by nitrogen or inert gas to react with the precursor powder for fluorination.

6. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 5, characterized in that: The temperature of the fluorination reaction is 300-700°C.

7. The method for preparing a high entropy phosphorus-fluoride nanoparticle catalyst according to any one of claims 3 to 5, characterized in that: The inert gas is Ar gas, and the Ar gas flow rate during the phosphating and fluoriding process is 50 ml / min; phosphating is performed first and then fluoriding, NaH2PO2 and NH4F are supplied in excess, the phosphating time is 2 to 3 hours, and the fluoridation time is 5 to 30 minutes.

8. The method for preparing the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 7, characterized in that: The ammonium hydroxide solution is selected from aqueous ammonia with an ammonia concentration of ≥20wt%.

9. The high entropy phosphorus-fluoride nanoparticle catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. An oxygen evolution electrode prepared using the high entropy phosphorus-fluoride nanoparticle catalyst according to claim 9.

Citation Information

Patent Citations

  • High-entropy alloy nano-catalyst and preparation method thereof

    CN118950028A

  • Catalyst for hydrogen-producing electrode in water electrolysis, catalyst for oxygen-producing electrode in water electrolysis, method for producing catalyst for water electrolysis, and method for electrolysis of water

    JP2024125620A